CFD analysis of temperature imbalance in full scale tangentially fired coal boiler - Fadhil S.S.A.; Hasini H.; Mohd Jaafar M.N. (Trans Tech Publications Ltd, 2023)
Tangentially fired boilers are widely used in generating electricity power due to its advantage of distributing heat evenly to all furnace walls. However, this type of boiler poses common temperature deviation at the upper furnace which may lead to temperature imbalance. This consequently may reduce the performance of the boiler which cannot be simply ignored. This paper investigates the flow and temperature imbalance in a 700 MW coal-fired boiler at full load and reduced load conditions. The effect of loading condition towards the temperature imbalance is investigated. It is observed that temperature imbalance occurs at the reheater plane between left wall and right wall where higher temperature was found near the left wall. Temperature imbalance is influenced by the loading condition, the higher the loading the higher the imbalance. © (2014) Trans Tech Publications, Switzerland.